Modular synthesis of the pyrimidine core of the manzacidins by divergent Tsuji–Trost coupling - Bretzke, Sebastian; Scheeff, Stephan; Vollmeyer, Felicitas; Eberhagen, Friederike; Rominger, Frank; Menche, Dirk (Beilstein Journal of Organic Chemistry, 2016)
The design, development and application of an efficient procedure for the concise synthesis of the 1,3-syn- and anti-tetrahydropyrimidine cores of manzacidins are reported. The intramolecular allylic substitution reaction of a readily available joint urea-type substrate enables the facile preparation of both diastereomers in high yields. The practical application of this approach is demonstrated in the efficient and modular preparation of the authentic heterocyclic cores of manzacidins, structurally unique bromopyrrole alkaloids of marine origin. Additional features of this route include the stereoselective generation of the central amine core with an appending quaternary center by an asymmetric addition of a Grignard reagent to a chiral tert-butanesulfinyl ketimine following an optimized Ellman protocol and a cross-metathesis of a challenging homoallylic urea substrate, which proceeds in good yields in the presence of an organic phosphoric acid.
Keywords: cross-metathesis; natural products; pyrimidines; Tsuji–Trost reaction; synthetic methods